Pengaruh Kualitas Layanan, Harga dan Gaya Hidup Terhadap Keputusan Pembelian Tiket Pesawat Melalui Traveloka (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang Tahun Angkatan 2018) - Ahmad Khoiru Rozikin; Muhammad Mansur; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this study is to test the influence of service quality, price and lifestyle on airfare purchasing decisions through Traveloka case study on students of the Faculty of Economics and Business of the Islamic University of Malang Year 2018. This study used the Malhotra formula to determine the number of samples so that 85 samples were obtained. Sampling techniques using accidental sampling methods obtained samples as many as 85 respondents. The data collection method in this study used questionnaires, data analysis techniques in this study using multiple linear regression analysis. The results showed that the quality of service, price and lifestyle simultaneously influenced the decision to purchase air tickets through Traveloka in students of the Faculty of Economics and Business of the Islamic University of Malang in 2018. In this study also showed that partially the quality of service, price and lifestyle influences the decision to buy air tickets through Traveloka on students of the Faculty of Economics and Business of the Islamic University of Malang in 2018. Keywords: quality of service, price, lifestyle, purchasing decision.